Traces of Runic Lore in Italy: The Wooden Calendar 'Book' in Bologna and Its Medieval Connections - Cucina, Carla (Classiconorroena, 2013)
This paper is the text of a public lecture, held at the National Museum of Denmark (23rd April 2009), dealing with a valuable and well-preserved runic calendar from the Museo Civico Medievale in Bologna. It is a late example of wooden ‘rimbok’, i.e. a portable calendar made up of different wooden tablets – each for one or more of the twelve months of the year – tied together in the form of a book. Typology and style of the artifact tell of a Swedish model, but its origin is to be placed in France. More detailed both in calendar information and in the iconographic apparatus than commonly seen in medieval Scandinavian wooden ‘rimbokar’ or ‘rimstavar’ (i.e. calendar sticks), the ‘runic book’ of Bologna rather shows some formal resemblance to the Swedish runic manuscript calendars preserved on parchment, and reveals peculiar closeness to a few other calendars of the same kind spread in European antiquarian collections. An introduction to the runic and iconographic features of the Italian calendar, also seen against the vast background of late and post-medieval runic and calendar lore in Western Europe, as well as a brief account of the circumstances of its being now part of the Medieval section of the Musei Civici in Bologna, form the main concern of the present article.